An inconvenient truth (DVD) - Gore, Albert 1948-; Guggenheim, Davis; David, Laurie; Bender, Lawrence; Burns, Scott Z.; Skoll, Jeff; Chilcott, Leslie; Richman, Bob; Cassidy, Jay; Swietlik, Dan; Brook, Michael musician (Paramount, 2006)
Former Vice President Al Gore explains the facts of global warming, presents arguments that the dangers of global warning have reached the level of crisis, and addresses the efforts of certain interests to discredit the anti-global warming cause. Between lecture segments, Gore discusses his personal commitment to the environment, sharing anecdotes from his experiences.